The Investigation of the Stability of the Granules Based on Arginine and Tincture of Ginseng - Katerina Romas (Journal of Global Pharma Technology, 2020)
The article presents the stability studies of the granules based on arginine and tincture of ginseng with neuroprotective (nootropic) action for the treatment of various disorders of the functional activity of the brain. For determining stability and shelf life of the developed medicine, several series of granules were stored at a temperature 15-25 °C in a dark, light protected place. Based on the research, it can be concluded that within 24 months from the date of manufacture, granules remain stable in all respects that have been studied.